Fabrication of New Hybrid Scaffolds for in vivo Perivascular Application to Treat Limb Ischemia - Carrabba, Michele; Jover, Eva; Fagnano, Marco; Thomas, Anita C.; Avolio, Elisa; Richardson, Thomas; Carter, Ben; Vozzi, Giovanni; Perriman, Adam W.; Madeddu, Paolo (Frontiers in Cardiovascular Medicine, 2020)
Cell therapies are emerging as a new therapeutic frontier for the treatment of ischemic disease. However, femoral occlusions can be challenging environments for effective therapeutic cell delivery. In this study, cell-engineered hybrid scaffolds are implanted around the occluded femoral artery and the therapeutic benefit through the formation of new collateral arteries is investigated. First, it is reported the fabrication of different hybrid “hard-soft” 3D channel-shaped scaffolds comprising either poly(ε-caprolactone) [PCL] or polylactic-co-glycolic acid [PLGA]) and electro-spun of gelatin (GL) nanofibers. Both PCL-GL and PLGA-GL scaffolds show anisotropic characteristics in mechanical tests and PLGA displays a greater rigidity and faster degradability in wet conditions. The resulting constructs are engineered using human adventitial pericytes (APCs) and both exhibit excellent biocompatibility. The 3D environment also induces expressional changes in APCs, conferring a more pronounced proangiogenic secretory profile. Bioprinting of alginate-pluronic gel (AG/PL), containing APCs and endothelial cells, completes the hybrid scaffold providing accurate spatial organization of the delivered cells. The scaffolds implantation around the mice occluded femoral artery shows that bioengineered PLGA hybrid scaffold outperforms the PCL counterpart accelerating limb blood flow recovery through the formation arterioles with diameters greater than 50 μm, demonstrating the therapeutic potential in stimulating reparative angiogenesis.